A Review of Patient Preferences for Osteoporosis Drug Treatment - Hiligsmann, Mickaël (Curr Rheumatol Rep, 2015)
Poor medication adherence is a major problem in chronic diseases such as osteoporosis that may partially be due to unaddressed patient values and preferences. Data on patient preferences could help clinicians to improve medication adherence and could also be useful in policy decisions and guideline development. This paper aims to identify literature reporting on the preferences of patients for osteoporosis drug medications. Several methods have been used to elicit patient preferences for medications and their characteristics including qualitative research, survey with ranking/rating exercises, discrete-choice experiments and clinical studies (crossover designs, open-label study). All these studies revealed that osteoporotic patients have preferences for medications and their attributes, in particular for less-frequent dosing regimens. Interestingly, variations in the preferences of patients were observed in most studies, suggesting the importance to take into account individual preference in decision-making to improve osteoporosis care.